Upaya Peningkatan Kompetensi Penulisan Karya Tulis Ilmiah dan Profesionalisme Guru di SMK Migas Insan Kamil, Kota Balikpapan - Lisnawaty Simatupang; Ria Setyawati; Nawang Retno Dwiningrum; Maria Veronika Simanjunta; Enita Rayu (Journal of Applied Community Engagement, 2025)
Government regulations and policies on teacher quality and competence are increasing. Teachers are expected to be more innovative in carrying out their teaching duties. However, teacher readiness to produce scientific work is still insufficient. Therefore, community service activities are held related to scientific writing training for teachers. Participants in the program were teachers and staff from SMK Migas Balikpapan. This training activity aims to: improve professionalism, inspire teachers to conduct research, and experiment with new teaching methods. As a result of this practice, the teacher's understanding of how to create and publish scientific writing improves. It can help teachers establish in their careers and contribute to the dissemination of information throughout the educational community.